Citation study of library and information science dissertations for collection development - Yeap, C.K.; Kaur, K. (Masters of Library of Inf. Sci. Program Uni. of Malaya, 2008)
This study applies citation analysis method to examine the use of information resources by students of the Master in Library and Information Science (MLIS) at the University of Malaya in preparing their dissertation. References from a sample of 40 MLIS thesis from the period 2000-2005 were examined for: year of publication; author; source title; bibliographic format; language; subject category; and place of publication. Core journal titles are compared with Journal Citation Report (JCR) listing and also for availability at the University of Malaya Library. The study shows that journals and books are still the most used sources for information and there is a steady increase in the use of electronic media by Library and Information Science (LIS) researchers. Authorship pattern indicates preference for single authored works. This study serves as a baseline indicator of resources used by LIS researchers. It can be utilised by librarians to focus on collection development to support research needs.